New Factors Predicting Delayed Graft Function: a Multi-Center Cohort Study of Kidney Donation After Brain Death Followed by Circulatory Death - Qipeng Sun; Zhengyu Huang; Honglan Zhou; Minzhuan Lin; Xuefeng Hua; Liangqing Hong; Ning Na; Ruiming Cai; Gang Wang; Qiquan Sun (Karger Publishers, 2018)
Background/Aims: Delayed graft function (DGF) is a common complication following kidney transplantation adversely affecting graft outcomes. Donation after brain death followed by circulatory death (DBCD), a novel donation pattern, is expected to correlate with high incidence of DGF. However, little information is available about factors associated with DGF in DBCD. Methods: A total of 383 kidney transplants from DBCD donation in three institutions were enrolled. Associations of DGF with the clinical characteristics of recipients and donors were quantified. Results: In this retrospective multi-center study, the incidence of DGF was 19.3%. Lower incidence of DGF was found in recipients for whom antithymocyte globulin was used for induction (p < 0.05), which was an independent protective factor against DGF (odds ratio [OR] = 0.48; 95% CI 0.27-0.86). Two novel explicative variables were recognized as independent risk factors, including use of vasoactive drugs (OR = 3.15; 95% CI 1.39-7.14) and cardiopulmonary resuscitation (OR = 2.51; 95% CI 1.05-6.00), which contributed significantly to increased risk of DGF (p < 0.05). Prolonged warm ischemia time (> 18 min; OR = 2.42; 95% CI 1.36-4.32), was also predictive of DGF in DBCD. A prediction model was developed and achieved an area under the curve of 0.89 in predicting DGF when combined with reported parameters. Conclusion: The novel factors, confirmed for the first time in our study, will help to improve risk prediction of DGF and to determine optimal interventions to prevent DGF in clinical practice.